2012
DOI: 10.1089/neu.2011.1938
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free DNA as a Marker for Prediction of Brain Damage in Traumatic Brain Injury in Rats

Abstract: Traumatic brain injury (TBI) is a major cause of morbidity and mortality, and early predictors of neurological outcomes are of great clinical importance. Cell free DNA (CFD), a biomarker used for the diagnosis and monitoring of several diseases, has been implicated as a possible prognostic indicator after TBI. The purpose of this study was to determine the pattern and timing of CFD levels after TBI, and whether a relationship exists between the level of CFD and brain edema and neurological outcomes. Thirty-nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 42 publications
3
32
0
2
Order By: Relevance
“…6,22 DNA fragmentation in the brain has also been reported after other forms of TBI, indicating that it may represent a shared final common pathophysiological mechanism of injury across a variety of brain insults. [12][13][14][15] The increased CFD observed in plasma after repeated blast exposures is also a somewhat novel finding. Increased plasma CFD has been reported after other forms of TBI as well as in patients with neurological abnormalities.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…6,22 DNA fragmentation in the brain has also been reported after other forms of TBI, indicating that it may represent a shared final common pathophysiological mechanism of injury across a variety of brain insults. [12][13][14][15] The increased CFD observed in plasma after repeated blast exposures is also a somewhat novel finding. Increased plasma CFD has been reported after other forms of TBI as well as in patients with neurological abnormalities.…”
Section: Discussionmentioning
confidence: 87%
“…Increased plasma CFD has been reported after other forms of TBI as well as in patients with neurological abnormalities. 12,[14][15][16][17]19,20 The maximum level of circulating CFD was observed at 2 h and was still significantly elevated at 6 h after repeated blast exposures, likely indicating a slow clearance after a transient release of CFD into the circulation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These molecules are released into the plasma due to various biological processes, including cancer, conferring a diagnostic vantage point without invasive biopsies (Van Der Vaart and Pretorius 2008). Multiple lines of evidence have shown that these nucleic acids can be used as biomarkers for a series of acute conditions, such as liver response to drug overdose (Wang et al 2009), heart attack (Creemers et al 2012), sepsis (Dwivedi et al 2012), and brain trauma (Ohayon et al 2012). Real-time bedside sequencing at relatively short intervals can serve as the basis for a universal apparatus to capture these biomarkers, adding a new layer of information to patient status.…”
Section: Health-related Applicationsmentioning
confidence: 99%